Initial growth of Megathyrsus maximus cv. Massai grass biostimulated with Burkholderia pyrrocinia at different sowing depths - Moraes, Lorena Maués; Lage Filho, Nauara Moura; Martins, Victoria de Lima; Costa, Daniel Sidney Araújo da; Silva, Gisele Barata da; Faturi, Cristian; Rêgo, Aníbal Coutinho do; Silva, Thiago Carvalho da (Acta Scientiarum. Animal Sciences, 2025)
Sowing depth affects both germination and emergence of seeds. Thus, inoculation with Burkholderia pyrrocinia, a biostimulant, may have positive effects on grass establishment. The aim was to evaluate the effects of inoculation with B. pyrrocinia (BP; without and with) and sowing depth (SD; 0, 1, 2, 3, 6, and 12 cm) on the initial growth of Megathyrsus maximus cv. Massai. Germination, emergence, and initial shoot and root growth were assessed. The evaluations were performed 21 days after planting. The germination percentage (%G) was affected by the BP×SD interaction (P<0.05), with the highest %G occurring at 4.11 cm and 4.90 cm when the seed was inoculated and not inoculated, respectively. The emergence speed index (ESI) was also affected by the interaction of the factors (p < 0.05), following a quadratic effect when inoculation was performed, with the highest ESI at a depth of 4.17 cm, while the absence of inoculation resulted in a linear ESI across the depths. However, the initial forage mass was not influenced by the treatments (p > 0.05), with an average production of 0.065 g. Inoculation with Burkholderia pyrrocinia combined with sowing depth enhances the initial growth of Megathyrsus maximus cv. Massai by increasing the germination percentage and emergence speed.